Assessment on different animal preservation techniques based on systematic decision tree for the development of natural history gallery in Pulau Tinggi Malaysia - Zahari, Fatin Nur Atikah (2022)
Natural history collection is significant to examine the environmental impacts from human activities. The contribution of the natural history collection has been discussed and praised in recent years. Yet in the scientific literature, there are lack of public records and publication regarding the management of natural history specimens especially in the aspect of preservation techniques. Thus, this study aims to evaluate the perception of subject matter experts (SMEs) on various preservation techniques, analyse the time taken and the cost of each technique, develop the systematic decision tree (SDT) model that analysed by practitioners and come out with a development plan of Natural History Gallery in Pulau Tinggi. Interview sessions with five SMEs were done and questionnaire was distributed to 13 practitioners by using semi-structured and structured questionnaire to collect qualitative and quantitative data. Five types of preservation techniques namely taxidermy, resin, pinning, preservation in alcohol and diaphonization were conducted and analysed using SDT. The outcomes from the analysis showed that there are three types of SDT model which are difficulty level, time taken and cost spent. The SDT model of difficulty level shows that pinning technique was found to be the easiest method while taxidermy is the most difficult technique. Practitioners agreed on taxidermy being the easy method, but they think preservation in alcohol is easier. As for the SDT model in term of time taken, diaphonization takes the longest time to complete the process while pinning takes the shortest time in preservation. Practitioners concur for diaphonization but they think preservation in alcohol takes the shortest time. While SDT for costing aspect shows that pinning requires the lowest expense while diaphonization needs the highest cost and practitioners do agree with the statement. All data acquired from this study is important and will be used as a guide for the development and improvement of natural history gallery in Malaysia.